Quality of life among patients after Hodgkin lymphoma treatment: a 3-year prospective study - B. B. Samura (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose of the study was to investigate the quality of life among patients after Hodgkin lymphoma treatment to estimate demographic, clinical, psychosocial risk factors of unfavorable prognosis depending on the occurrence of cardiovascular events.